2005
DOI: 10.3354/meps287189
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and life history of Hemimysis margalefi (Crustacea: Mysidacea), a ‘thermophilic’ cave-dwelling species benefiting from the warming of the NW Mediterranean

Abstract: Dark submarine caves are an extreme and fragmented habitat in which mysids (Crustacea: Mysidacea) of the genus Hemimysis can be found. Hemimysis speluncola has long been the dominant mysid species of the NW Mediterranean caves, but with the recent warming of this region, its congener H. margalefi has replaced it. Nothing is known about the biology and ecology of H. margalefi and here, we provide the first information about its demographic structure and reproductive biology in a cave recently affected by the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Mysids were sampled using a hand-operated suction bottle (Chevaldonné et al 2008), then identified and sorted in vivo under a dissecting microscope. When possible, juveniles and adults (immature and mature) were separated following Tattersall & Tattersall (1951) and Lejeusne & Chevaldonné (2005), since their diet may differ (Takahashi 2004). When not possible, only adults were used.…”
Section: Samplingmentioning
confidence: 99%
“…Mysids were sampled using a hand-operated suction bottle (Chevaldonné et al 2008), then identified and sorted in vivo under a dissecting microscope. When possible, juveniles and adults (immature and mature) were separated following Tattersall & Tattersall (1951) and Lejeusne & Chevaldonné (2005), since their diet may differ (Takahashi 2004). When not possible, only adults were used.…”
Section: Samplingmentioning
confidence: 99%
“…In the two Mediterranean caves from which we collected A. hypogea (Jarre and 3PP), the most abundant species of cave-dwelling mysids are Hemimysis margalefi and H. speluncola Ledoyer, 1963. The first is very abundant in both caves (Lejeusne & Chevaldonné 2005;Rastorgueff et al 2014) whereas the latter is now only found in 3PP cave due to regional warming of the Mediterranean Sea (Chevaldonné & Lejeusne 2003). In situ observations (Fig.…”
Section: Diet Of a Hypogea In Mediterranean Undersea Cavesmentioning
confidence: 97%
“…The use of steppingstone relay habitats between large caves has also been proposed to explain why the rare, inner-cave mysid H. mariannae displays a lower genetic structure than H. margalefi Lejeusne and Chevaldonné, 2006;Rastorgueff et al, 2014). H. margalefi needs to live in large swarms (Allee effect; Lejeusne and Chevaldonné, 2005) and therefore presents a narrower ecological niche than the solitary H. mariannae able to use any suitable crevicular habitat as a stepping stone Rastorgueff et al, 2014).…”
Section: Habitat Discontinuity and Population Connectivity At Microscalementioning
confidence: 98%